Particulate Matter Air Pollution and Racial Differences in Cardiovascular Disease Risk. Issue 4 (April 2018) - Erqou, Sebhat; Clougherty, Jane E.; Olafiranye, Oladipupo; Magnani, Jared W.; Aiyer, Aryan; Tripathy, Sheila; Kinnee, Ellen; Kip, Kevin E.; Reis, Steven E.
Abstract : Objective—: We aimed to assess racial differences in air pollution exposures to ambient fine particulate matter (particles with median aerodynamic diameter <2.5 µm [PM2.5 ]) and black carbon (BC) and their association with cardiovascular disease (CVD) risk factors, arterial endothelial function, incident CVD events, and all-cause mortality. Approach and Results—: Data from the HeartSCORE study (Heart Strategies Concentrating on Risk Evaluation) were used to estimate 1-year average air pollution exposure to PM2.5 and BC using land use regression models. Correlates of PM2.5 and BC were assessed using linear regression models. Associations with clinical outcomes were determined using Cox proportional hazards models, adjusting for traditional CVD risk factors. Data were available on 1717 participants (66% women; 45% blacks; 59±8 years). Blacks had significantly higher exposure to PM2.5 (mean 16.1±0.75 versus 15.7±0.73µg/m 3 ; P =0.001) and BC (1.19±0.11 versus 1.16±0.13abs; P =0.001) compared with whites. Exposure to PM2.5, but not BC, was independently associated with higher blood glucose and worse arterial endothelial function. PM2.5 was associated with a higher risk of incident CVD events and all-cause mortality combined for median follow-up of 8.3 years. Blacks had 1.45 (95% CI, 1.00–2.09) higher risk of combined CVD events and all-cause mortality than whites in models adjusted for relevant covariates. This association was modestly attenuated with adjustment for PM2.5 . Conclusions—: PM2.5 exposure was associated with elevated blood glucose, worse endothelial function, and incident CVD events and all-cause mortality. Blacks had a higher rate of incident CVD events and all-cause mortality than whites that was only partly explained by higher exposure to PM2.5 . Abstract : Supplemental Digital Content is available in the text.